1986
DOI: 10.1037/0003-066x.41.7.794
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient alcoholism treatment: Who benefits?

Abstract: Although uncontrolled studies have yielded mixed findings, 26 controlled comparisons have consistently shown no overall advantage for residential over nonresidential settings, for longer over shorter inpatient programs, or for more intensive over less intensive interventions in treating alcohol abuse. Predictor data suggest that intensive treatment may be differentially beneficial for more severely deteriorated and less socially stable individuals. The outcome of alcoholism treatment is more likely to be influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
115
0
3

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(124 citation statements)
references
References 55 publications
6
115
0
3
Order By: Relevance
“…These findings are consistent with literature showing that, over time, clients entering drug abuse treatment tend to show improved outcomes (Hubbard et al, 1989;Miller and Hester, 1986;Simpson and Sells, 1990). The absence of CIU effects or CIU by time interactions suggests that, while both CIU and non-CIU groups improved, one group did not improve more than the other.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These findings are consistent with literature showing that, over time, clients entering drug abuse treatment tend to show improved outcomes (Hubbard et al, 1989;Miller and Hester, 1986;Simpson and Sells, 1990). The absence of CIU effects or CIU by time interactions suggests that, while both CIU and non-CIU groups improved, one group did not improve more than the other.…”
Section: Discussionsupporting
confidence: 82%
“…Two-thirds of all substance abuse treatment is provided in the public sector (Mechanic, Schlesinger and McAlpine, 1995). Treatment has been shown effective in reducing drug and alcohol use, in ameliorating associated health and social problems among those treated (McLellan, Luborsky, O'Brien, Woody and Druley, 1982;Hubbard et al, 1989;Miller and Hester, 1986;Simpson and Sells, 1990), and in reducing economic costs associated with substance abuse (Finigan, 1996;Gerstein et al,1994).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the series of comparisons between in-patient, residential and outpatient settings of addiction treatment (e.g. Miller & Hester 1986;McKay et al 1995) simply do not make sense from a continuing care perspective. Again, if treatments are expected to produce symptom reduction only as long as the patient is actively involved in that treatment, then there should be no post-treatment differences among patients assigned to any of those modalities-the common finding from these evaluations (see McLellan et al 1996).…”
Section: If Addiction Is Best Considered a Chronic Condition Then Wementioning
confidence: 99%
“…24,25 One exception to this is the study by Walsh et al, 26 which showed that among workers referred to an employee assistance program, those who were randomly assigned to a 3-week inpatient alcohol treatment program had significantly better alcohol-related outcomes than workers who were assigned to mandatory AA attendance only. Workers assigned to a third group were allowed to choose their treatment and had outcomes intermediate between the other two groups.…”
Section: Rehabilitationmentioning
confidence: 99%